Effect Of Potassium Koetjapate, A Drivative Of Koetjapic Acid Isolated From Sandoricum Koetjape Merr. On Human Colorectal Cancer. - Jafari, Seyedeh Fatemeh (2018)
In the present study an attempt was made to enhance the aqueous solubility of KA and to study its anti-colon cancer efficacy using in vitro and in vivo methods. Potassium salt of KA i.e., potassium koetjapate was prepared by semi-synthetic method. Anticancer activities of potassium koetjapate were compared with the native compound i.e., KA. MTT cell viability assay was used to obtain and compare the IC50 values of both the compounds. Pro-apoptotic effects of potassium koetjapate were assessed using caspases (3/7, 8 and 9), Hoechst 33342 and Rhodamine 123 fluorescent staining assays. Human apoptosis proteome profiler array was used to identify the protein targets responsible for the induction of apoptosis. Furthermore, in vitro antitumor effects of potassium koetjapate were studied using hanging drop assay. Three doses of potassium koetjapate (25, 50, and 100 mg/kg body weight) were tested in athymic nude mice model to study the in vivo anti-tumorigenic efficacy of potassium koetjapate. In this study, various formulations of KA were prepared. Solubility studies revealed that resultant KA derivative i.e. potassium koetjapate had better aqueous solubility than the solid dispersions of KA. In vitro anticancer studies revealed that potassium koetjapate has better cytotoxic activity than KA and its solid dispersion complex towards HCT 116 cell line.